Industrial policy and competitiveness in open economies - Ramos, Joseph (UN SantiagoCL, 1997)
Examines two major features of the region's economies: first, the process of liberalization and restructuring, which has been moving forward since the mid-198os and, second, the huge productivity gap between the region's firms and those enterprises operating in accordance with international standards of best practice in the developed world. The implications of these two features can serve as guidelines for the design of an ' industrial policy' for open economies.